The Meaning of Jihad in Abu Obaida's Oration on The Palestinian Conflict - Agus Sulaiman; Abdul Muntaqim Al Anshory; Nur Hasaniyah (Al-Muyassar: Journal of Arabic Education, 2024)
This article examines the meaning of jihad conveyed in Abu Obaida's oration during the conflict in Palestine. The research background covers the historical and political context of the region, as well as the relevance of Abu Obaida's role in inspiring resistance movements. The purpose of this study is to analyze Abu Obaida's understanding of jihad to Hamas forces, Palestinians, Muslims, Arab leaders, the World Security Council (UN) and Jihad through social media. The oration explained the social and political factors that influenced his views, as well as encouraged the impact of his oration on the movement in Palestine. The research methods used were the analysis of the content of Abu Obaida's oration, the study of related literature, and the opinions of historical and political experts. The data were analyzed qualitatively to understand the context, meaning, and implications of Abu Obaida's oration. The results showed that Abu Obaida interpreted jihad as a struggle for justice, liberation, and the rights of the Palestinian people. This understanding is reflected in the historical context and political conflicts facing Palestine. His oration succeeded in mobilizing and inspiring his audience, strengthening the spirit of resistance. The conclusion of this article presents a comprehensive overview of the meaning of jihad in the context of the Palestinian conflict through Abu Obaida's oration. This understanding provides deep insight into the factors shaping jihadist views in the conflict and can be a foundation for understanding the dynamics of movements in the region.